Roles of periaqueductal gray and nucleus raphe magnus on analgesia induced by lappaconitine, N-deacetyllappaconitine and morphine - GUO Xin; TANG Xi-can (Acta Pharmacologica Sinica, 2016)
In the rat tail flick test, ip LA 6 mg/kg, icv DLA 60 micrograms and icv or with morphine 5 micrograms exhibited significant analgesia. But with either LA 40 micrograms or DLA 60 micrograms was inactive. Naloxone (4 micrograms icv) which antagonized morphine analgesia failed to alter the analgesia induced by LA and DLA. Microinjection of DLA 20 micrograms or morphine 5 micrograms into the periaqueductal gray (PAG) or nucleus raphe magnus (NRM) produced markedly analgesic activity. The effects of electrolytic and kainic acid (0.8 micrograms) lesions of the PAG and NRM on the analgesia elicited in the rat from ip LA, icv DLA and morphine were also evaluated. No change in baseline tail flick latency was observed following lesions of the PAG and NRM. But lesions of the PAG and NRM significantly attenuated the analgesia mediated by LA, DLA and morphine. These results suggest that supraspinal sites, especially the PAG and NRM, are involved in the analgesic action induced by LA, DLA and morphine.